2022
DOI: 10.1021/acs.cgd.2c00123
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystallization of Curcuminoids with Hydroxybenzenes Pyrogallol and Hydroxyquinol: Investigations of Binary Thermal Phase Behaviors

Abstract: The binary thermal phase behaviors of the curcuminoids (CURDs) curcumin (CUR), demethoxycurcumin (DMC), and bis-(demethoxy)curcumin (BDMC) with either pyrogallol (PYR) and hydroxyquinol (HYQ) as potential cocrystal formers were investigated. Earlier, it was reported that CUR and BDMC form cocrystals in a 1:1 stoichiometric ratio with the aforementioned coformers. Here, we report for the first time cocrystallization experiments of DMC. Two different cocrystallization techniques, namely, liquid-assisted grinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Table 1 summarizes the results of interactions of cocrystals with coformers forced by external stimuli (grinding, melting, spinning). As one can see, the ET: EMA cocrystal is the most stable and neither GLU nor MAL can the ideal liquidus lines for ET (black) and the coformer (blue) as well as the predicted cocrystal melting behaviour (dashed red line) calculated using the Schroeder-van Laar and Prigogine-Defay equations, [57] respectively. Experimental points are represented by black diamonds (ET), blue inverted triangles (coformer), red triangles (cocrystal), magenta and orange circles (eutectic), grey squares (metastable eutectic).…”
Section: Coformers Exchange Specific Selectionmentioning
confidence: 99%
“…Table 1 summarizes the results of interactions of cocrystals with coformers forced by external stimuli (grinding, melting, spinning). As one can see, the ET: EMA cocrystal is the most stable and neither GLU nor MAL can the ideal liquidus lines for ET (black) and the coformer (blue) as well as the predicted cocrystal melting behaviour (dashed red line) calculated using the Schroeder-van Laar and Prigogine-Defay equations, [57] respectively. Experimental points are represented by black diamonds (ET), blue inverted triangles (coformer), red triangles (cocrystal), magenta and orange circles (eutectic), grey squares (metastable eutectic).…”
Section: Coformers Exchange Specific Selectionmentioning
confidence: 99%
“…The samples were blended with dry potassium bromide, maintaining a weight ratio of 1:100. Subsequently, this mixture was compacted into pellets, and the infrared absorption spectra of the samples were measured in the range of 4000 cm−1 to 600 cm−1 [36][37][38].…”
Section: Fourier Transform-infrared Spectroscopy Analysismentioning
confidence: 99%
“…Formation of hydrogen bonding between hydroxyl group of phenol and the keto group of CUR is responsible for the emerging cocrystals with pyrogallol (PYR), resorcinol (RES), phloroglucinol (PHL), quinol (HYQ), and hydroxyquinol (HXQ) which has been reported in the literatures. , It has been found that CUR–PYR cocrystal dissolves about 12 times faster than CUR which is the greatest solubility among the reported CUR pharmaceutical solids including polymorphs, cocrystals, and eutectics . Besides, in animal models, CUR–PYR displays less toxicity and more bioavailability during the high dose administration. , PYR, an active ingredient of the native Indian gooseberry Emblica fruit, has been widely used in Asian traditional medicine whose antioxidant and anti-inflammatory properties have been reported in several studies. , Providing that PYR is a potent drug for inhibition in the growth of lung cancer tumor, CUR–PYR has also been considered as a drug–drug cocrystal.…”
Section: Introductionmentioning
confidence: 99%